WHAT FACTORS DETERMINE ACCOUNTING STUDENTS PERCEPTION ON ACCOUNTING ETHICAL ISSUES? - Yunisa, Rine Rizky; Nurfauziah, Farah Latifah (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2023)
There are still several scandals associated with code of conduct offenses. It highlights the importance of ethical behavior. The aim of this project is to see about the ethical perspective of an accounting student influenced by the religiousness, passion for currency and etiquette sensibility. The research utilized primarily data from the respondent questionnaires with a sample of 92 respondents.. Methods utilized in this experiment are Quantitative methods by SPSS statistical analysis using a Likert scale. The technique used in this test is the reliability test, Validity Test, Classical Assumption Test, Hypothesis Test. The results of the analysis showed that Religiousness, passion of money and simultaneous ethical awareness influence positively on the moral perception of accountancy students..